DOP37 Efficacy and safety of filgotinib in patients with Ulcerative Colitis stratified by age: Post hoc analysis of the phase 2b/3 SELECTION and SELECTIONLTE studies. (21st January 2022) - Schreiber, S; Loftus, E V; Maaser, C; Danese, S; Rudolph, C; Jongen, R; De Haas, A; Oortwijn, A; Vermeire, S
Abstract: Background: With a growing prevalence of inflammatory bowel disease (IBD) in elderly patients, there is a clinical requirement to understand the impact of treatment in this population. 1 Filgotinib (FIL) is an oral Janus kinase 1 preferential inhibitor. This post hoc analysis of data collected in the phase 2b/3 SELECTION programme evaluated the efficacy and safety of FIL in patients with ulcerative colitis (UC) stratified by age. Methods: The SELECTION programme includes two Induction Studies, a Maintenance Study (NCT02914522) and a long-term extension (LTE) study (NCT02914535). Adults aged 18–75 years with moderately to severely active UC were randomized 2:2:1 to receive FIL 200 mg or 100 mg or placebo once daily for 11 weeks. Responders at week 10 were re-randomized 2:1 to continue assigned FIL treatment or placebo from week 11–58. In LTE, patients with disease worsening and those completing week 58 continued assigned treatment before receiving open-label FIL. We assessed the efficacy and safety of FIL at any dose in the overall cohort of SELECTION and LTE, stratified into five age groups: <30, ≥30–<40, ≥40–<50, ≥50–<60 and ≥60 years. Clinical remission was evaluated at week 10 and pMCS remission was assessed at week 10, 58 and LTE weeks 2, 4, 12 and 24. Exposure-adjusted incidence rates (EAIRs) were calculated for adverse events (AEs). A data cut-off of 28 February 2020 was used. Results: Baseline disease activity and previous and concomitant treatments were comparable across age groups in each treatment arm. While there were fewer patients in the ≥60 years group, patient distribution was similar in all other age groups. FIL induced clinical ( 16%) and pMCS ( 36%) remission in similar proportions of patients across all age groups at week 10 (Figure 1 ). At week 58, pMCS remission was achieved in 53% of FIL-treated patients across age groups (Figure 2 ). In LTE, the proportion of FIL-treated patients in pMCS remission generally increased with time and remained similar across all age groups (Figure 3 ). FIL-treated patients aged ≥60 years had higher EAIRs of any AE, infections, herpes zoster, malignancies, NMSC and MACE than younger patients (Table ). One thromboembolic event occurred in a FIL-treated patient aged <30 years. Three deaths related to cardiovascular disease occurred in FIL-treated patients aged ≥50 years. Conclusion: These findings suggest FIL is efficacious in inducing and maintaining symptomatic remission and could have an acceptable safety profile in adults with UC of all ages, including ≥60 years old. Age-related increases in incidences of certain AEs might be expected in patients with IBD; however, the number of patients ≥60 years limits comparison of these data with reported rates. Reference: 1 Zammarchi et al . BMC Gastroenterol 2020;20;147